Implementasi Prinsip Keadilan dalam Pengelolaan Dana Kemahasiswaan - Lake, Willem Batista; Hapsari, Aprina Nugrahesty Sulistya (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
The aim of this study was to determine the extent of the implementation of the principles of justice in managing funds in the scope of student organizations. The object of this research is Student Affairs at Faculty X, ABC University. The method used in this research is descriptive qualitative. This study uses primary data types by conducting data collection techniques in the form of interviews, observation and documentation. Interviews in this study were conducted with the committee and member of the Student Affairs Organization functionaries. The results of this study indicate that the application of the principle of justice has not been maximally implemented. This is based on predetermined indicators. The cause of not optimal implementation of the principle of justice in the management of student funds is the prejudice that the distribution of funds is still inequality and inconsistencies in Standard Operating Procedures for submitting and accountability for budget proposals by the committee.